Gospodarka samorządowa jako obiekt zarządzania - Bandelak-Rosłonkiewicz, Dominika; Kaczmarek, Bogusław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article is an analysis of two main issues: local government activities determining a position of self-government in a socio-economic system of the country; a necessity of professional approach to management of local government entity from the point of view of a wider system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 30-36